Exploring Wear Characteristics of AISI 1045 Steel under Variable Disc Rotation Speeds: A Tribological Investigation - Afif, Ilham Yustar; Jamari, Jamari; Saputra, Eko; Saefudin, Slamet; Subri, Muhammad; Amin, Muh. (TEKNIK, 2024)
Reliable mechanical components are the desired final product. When mechanical components come into contact with each other, there is a possibility of failure. Contact between components can result in friction leading to wear. Friction and wear can be studied through the science of tribology. The aim of this paper is to investigate the wear of AISI 1045 steel using a pin-on-disc tribometer with varying disc rotation speeds (rpm), to calculate the values of wear volume and specific wear rate. This research demonstrates that variations in disc rotation speed influence changes in sliding distance, wear width, wear volume, and specific wear rate on AISI 1045 steel pin. The conclusion drawn from this study is that as the disc rotation speed increases, the wear volume increases, and the specific wear rate decreases.